Conceptualizing a political dynasty index at the local level and its relation with the good governance index - Manalo, Abraham J.; Villamejor-Mendoza, Maria Fe (Quezon City National College of Public Administration and Governance, University of the Philippines Diliman, 2019)
Politcal dynasty is a pervasive phenomenon in Philippine society, economy, and polity. Based on concepts from institutional approach to public administration, the the dissertation conceptualized a Politcal Dynasty Index at the Local Level (PDILL) as a means to measure the political dynasty at the provincial level and determine its relation to the Good Governance Index (GGI). The index was populated with data gathered from the 38 provinces of Luzon, excluding Metro Manila, that were primarily sourced from the Statement of Assets, Liability and Net Worth (SALN) forms of elected local government officials safekept at the Office of the Ombudsman.
Three factors determine the strength of political dynastization in a province: (a) expansiveness of its political dynastization, or the collective mass of all political dynasties in in the province; (b) cumulative length of existence of political dynasties in said province, and (c) dominance of its political dynastization, or the concentration of strength among competing political dynasties in the province in comparison to those existing in other provinces. Different PDILL models were built on these factors, depending on the attribute being highlighted. In turn, the PDILL models showcased the individual and comparative strength of political dynastization among the 38 Luzon provinces.
Based on inferential analysis performed, the study discovered that the relationship between strength (specifically expansiveness) of politcal dynastization in a province and provincial GGI is non-linear. There exists a threshold in the expansiveness of political dynastization, such that below the threshold, the association between expansiveness and GGI is found to be very strong inversem while above it, the relationship becomes direct but weak. As importantly, the study was able to identify the intervening variables that dampened the initial very strong negative association between dynastic expansiveness and the practice of good governance among the 38 Luzon provinces.
Thesis (Doctor of Public Administration)--University of the Philippines Diliman
Keywords: Political indicators -- Philippines; Families -- Political activity -- Philippines; Elections -- Corrupt practices -- Philippines; Local government -- Philipines; Political culture -- Philippines; Philippines -- Politics and government; Political dynasty